Pengaruh Latihan Aerobik Intensitas Sedang terhadap Kadar Nox Plasma dan Tekanan Darah Istirahat pada Wanita Lansia Overweight - Sri Mukti Suhartini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Aging is a dominant risk factor for most forms of cardiovascular disease. Sedentary lifestyle in elderly with obesity can decrease the function of cardiovascular system. Previous study determined that moderate intensity aerobic exercise was highly recommended in elderly because the type of exercise can improve body fitness and oxidative damage due to aging. The aims of this study was to investigate the effect of moderate intensity aerobic exercise on NOx plasma level, systolic blood pressure (SBP) and diastolic blood pressure (DBP) in sedentary elderly women with overweight. The research method is quasi experimental with pre test and post test design. The sample included 33 volunteer sedentary elderly women overweight with age 65,11±4,85 years old that divided on two group that is the experimental group (EG/ n=17) and control group (CG/ n=16). EG performed moderate intensity aerobic exercise (walking) during 30 min per session, intensity 50–80% heart rate maximum, three times per week for 12 week. The examination of NOx plasma level by ELISA method and resting blood pressure by auscultation method. Data was processed by unpaired t-test. Experimental group had significantly lower level of SBP (-10,294 p 0,001) than CG. NOx plasma level showed significantly decreases in both group (p < 0,05), but the decreasing trend was found to be higher in the CG. DBP and body mass index (BMI) did not change (p >0,05). Moderate intensity aerobic exercise can delay the reduction of NO due to aging proceses.